Frequency Analysis of Noise Generated by Pneumatic Wheels - WARCZEK, Jan; BURDZIK, Rafał; KONIECZNY, Łukasz; SIWIEC, Grzegorz (Archives of Acoustics, 2017)
The dominant sources of traffic noise, which are linked directly to the vehicle, are dependent on the speed. In terms of speed of 50–120 km/h the dominant source of noise is pneumatic wheels. The aim of the research was chosen to develop a method and experimental determination of the dominant frequency components of noise generated by the car tire. For the purpose of the study and on the basis of the analysis of the source data it was assumed that there is a relationship between the vibration of the tread elements and emitted noise, especially for low and medium frequencies. Thus, the target was set on the basis of the own method of research in the built measuring station. Based on the survey and the obtained results it can be stated that in the spectrum of the noise emitted by the tires the frequency componentsare dominant. Non-directional tire structure includes more frequency components which at the speed adopted in the studies are located at a greater frequency range than it is for the directional tire. In the case of a tire with a directional tread, acoustic emission energy is more associated with specific frequency components. The developed method provides results independent from the influence of the type of road surface on the acoustic emission while driving.